One-Pot Synthesis of Levulinic Acid/Ester from C5 Carbohydrates in a Methanol Medium - Hu, Xun; Song, Yao; Wu, Liping; Gholizadeh, Mortaza; Li, Chun-Zhu (American Chemical Society, 2013)
A process for direct conversion of xylose to methyl levulinate and levulinic acid has been developed in this study. A methanol medium, solid acid catalyst Amberlyst 70, and hydrogenation catalyst Pd/Al2O3 were used to direct xylose to follow the designed route to the target products. The methanol medium can prevent the hydrogenation of xylose to xylitol via the transformation of xylose into methyl xylosides. Amberlyst 70 catalyzes the dehydration of methyl xylosides into furfural, while Pd/Al2O3 catalyzes the hydrogenation of furfural into furfuryl alcohol. The hydrolysis/methanolysis of furfuryl alcohol over Amberlyst 70 produces levulinic acid/ester. Among these steps, the hydrogenation of furfural is the one determining the overall selectivity from xylose to levulinic acid/ester. The ideal hydrogenation catalyst needs to be selective to hydrogenate only the carbonyl group of furfural but not the furan rings.